Metagenomics of the water column in the pristine upper course of the Amazon river. - Rohit Ghai; Francisco Rodriguez-Valera; Katherine D McMahon; Danyelle Toyama; Raquel Rinke; Tereza Cristina Souza de Oliveira; José Wagner Garcia; Fernando Pellon de Miranda; Flavio Henrique-Silva (PLoS ONE, 2011)
River water is a small percentage of the total freshwater on Earth but represents an essential resource for mankind. Microbes in rivers perform essential ecosystem roles including the mineralization of significant quantities of organic matter originating from terrestrial habitats. The Amazon river in particular is famous for its size and importance in the mobilization of both water and carbon out of its enormous basin. Here we present the first metagenomic study on the microbiota of this river. It presents many features in common with the other freshwater metagenome available (Lake Gatun in Panama) and much less similarity with marine samples. Among the microbial taxa found, the cosmopolitan freshwater acI lineage of the actinobacteria was clearly dominant. Group I Crenarchaea and the freshwater sister group of the marine SAR11 clade, LD12, were found alongside more exclusive and well known freshwater taxa such as Polynucleobacter. A metabolism-centric analysis revealed a disproportionate representation of pathways involved in heterotrophic carbon processing, as compared to those found in marine samples. In particular, these river microbes appear to be specialized in taking up and mineralizing allochthonous carbon derived from plant material.